Problem representations and collective mind within networks - Ogundipe, Samuel Johnson (2020)
This dissertation is primarily motivated by the shortage of research in business network context that focuses on explaining how shared understanding and collective cognition develop in business relationships. The study is rooted in a broader research agenda that investigates the interplay between human cognition, action, and outcome. However, despite the central position of this body of work within the context of relationship management, the conceptual evolution has been mainly about individual subjective cognition – e.g. manager’s network insights or network picture. Consequently, marketing scholars have invested a considerable research effort in individuals and dyads with relatively limited attention to the overall networks’ collective perspectives.